Government Spending and Poverty Reduction in Vietnam - Fan, Shenggen; Huong, Pham Lan; Long, Trinh Quang (World Bank, Washington, DC, 2016)
The objective of this study is to analyse the impact of various types of government spending on growth and poverty reduction, using provincial level data over the last decade. Government spending reduces poverty through many channels such as agricultural growth and improved nonfarm employment. We will try to capture all these different effects in the analysis if the data allow. This paper opens with a review of Vietnam’s economic reforms and growth over the past decade. We then sketch Vietnam’s poverty profile, highlighting changes over time, regional distribution, and differences among population groups. In the next two chapters, we will review the trend and composition of government spending, agricultural R&D and infrastructure endowments in Vietnam over the last decade. Chapter 5 presents the analytical framework used to estimate the effect of various types of government spending on growth and poverty reduction. The data, model estimation, and results are presented in chapter 6. We conclude the paper by offering future priorities for government investments in chapter 7.